The relationship of domestic pet ownership with the risk of childhood asthma: A systematic review and meta-analysis - Ji, Xiaoyi; Yao, Yuan; Zheng, Ping; Hao, Chuangli (Frontiers in Pediatrics, 2022)
Background and Objective: The relationship between pet ownership and childhood asthma remains controversial. In recent years, there have been increasing studies with large sample size. Therefore, we conducted this systematic review and meta-analysis to evaluate the relationship between pet ownership and childhood asthma. Method: Relevant research was retrieved from PubMed, Cochrane, EMBASE, and Web of science. The retrieval was as of October 1, 2021. The Newcastle-Ottawa Scale (NOS) was used to assess the quality of the included studies. Stata 15.0 was used to conduct the meta-analysis. Results: A total of 60 studies with large sample size published between 1995 and 2021 were included in this systematic review and meta-analysis, which included 18 cohort studies and 42 case-control studies covering 27 countries and 1,871,295 children. As shown by meta-analysis results, cat ownership (OR=1.18 , 95%CI: 1.05~1.33 ) and dog ownership (OR=1.12 , 95%CI: 1.0 0~1.24 ) have a significant bearing on the occurrence of childhood asthma. Pet ownership was also positively correlated with the occurrence of severe childhood asthma ( OR=1.15, 95%CI: 1.11~1.20) Conclusion: Pet ownership, especially cats and dogs, is associated with the occurrence of asthma in children.